Natuurmonumenten als cultuurmonumenten. De voortdurende verandering van het begrip natuur in onze cultuur (Bulletin KNOB, 2011)
Dutchmen have not so much created the Netherlands as caused it. The historical landscapes are compromises between what was possible and what was desirable. The last attack on unused or sparsely used wasteland was less than one and a half century ago. Since then wasteland has been called nature conservation area. Increasing scarcity of such areas was regretted by more and more people. In a number of phases defensive protection against bringing nature into cultivation developed into an offensive that 'returned' cultivated land to nature. According to many authors this development started with the foundation of the Society for the Preservation of Nature in the Netherlands in 1905. Since the forties a national policy has started to develop, which also involved nature conservation in its assessments on physical planning. In the seventies nature conservation as a mass movement came into vogue.Nature and a more natural life were becoming priorities for more and more people, while fear of environmental disasters and resistance against new motorways and polluting industry increased. In the eighties nature conservation was becoming more powerful and a start was made with the conversion of natural landscape into 'new nature'. In the nineties an increasing number of binding European and international treaties came into effect. The present government thinks that this is the reason why the country threatens to be locked up and tries to interpret the regulations as flexibly as possible and to economize strongly on nature. Now that nature has been forced onto the defensive, the time seems to have come when nature reserves should be able to claim protection as cultural heritage as well. For the first phase Naardermeer is the best candidate, for the second the area around Posbank and for the third Deelerwoud. The most important recently developed nature reserve is the island of Tiengemeten, which is a perfect illustration of the views and types of nature that were considered desirable and possible to make around the turn of the century.